Influence of Textbooks and Peer-Provided Activities on Learning Outcomes of At-risk Mathematics Students - Jeje, Olusola Samuel; Gbenro, Sunday Oluwaseun; Olagoke, Michael (IJRDO- Journal of Educational Research, 2019)
Improving achievement gains of students has been a major concern for teachers all over the world. Varying students’ learning strategies, amount of time spent on academic materials, and active participation in the classroom have been observed to impact learning outcomes. The study compared the influence of textbook and peer-provided activities on the performance of at-risk mathematics students among the junior secondary schools in Ekiti state. A quasi-experimental pretest-posttest design was adopted. The sample for the study consisted of one hundred and twenty (120) at-risk mathematics students randomly selected through purposive randomization from twelve (12) junior secondary schools across the three senatorial districts in Ekiti State. The at-risk mathematics students were selected based on their performance in the General Mathematics Ability Test (GMAT) conducted two weeks prior to the commencement of the experiment. A Mathematics Achievement Test (MAT) was used to collect the data for the study. Four research questions were formulated and the research hypotheses were tested using analysis of variance (ANOVA), and Analysis of Covariance (ANCOVA) at the 0.05 level of significance. The study revealed that learning outcomes of at-risk mathematics students improved significantly with the use of peer-provided activities than with the use of textbook. Furthermore, the retention ability of at-risk mathematics students taught with peer-provided activity was significantly better than those taught with textbook. The study recommended that mathematics teachers in junior secondary schools should adopt peer tutoring strategy to enhance performance of at-risk mathematics students. The findings of this study shows that peer tutoring fosters improved learning outcomes, better competence, and improved cooperation among at-risk mathematics students.